Opinion and Preferences of Farmers regarding the services of Private Extension Service Providers - ltigi Prabhakar,; M. A. Ansari, (Journal of Agricultural Extension Management, 2025)
Due to systemic, financial and manpower constraints, the ·public extension system has been rendered ineffective, inadequate and insensitive to the needs and demands of farmers. Consequently, a number of private agencies have emerged providing agri-input and advisory services. Tarai region of Uttarakhand, known as the food bowl of the state, has also seen the emergence of such agencies. Among them, three Private Extension services providers (PESPs) viz. Hariyali Kisan Bazaar, e-Choupal and Tata Kisan Sansar are more popular among the farming community. The present study was undertaken in Udham Singh Nagar district of Uttarakhand with the objective of finding out the opinion and preferences of farmers regarding the services of PESPs. A sample size of sixty farmers was selected based on simple random sampling technique from the list of clientele farmers of these agencies. Data was collected through structured interview schedule. The findings reveal that farmers were not completely dependent on PESPs for information and services. This implies that the public extension system is still perceived to be a reliable source of information and services. However, PESPs can play a complementary role in supplementing public extension system but cannot substitute it completely. With respect to limitations, majority of the respondents reported 'High cost of service as a major problem with PESPs followed by 'Lack of assurance in quality of service/ information'. It was also found that 'Farm and Home visit' was the most widely used extension method by PESPs. Regarding preferences for various extension methods it varied from farmer to farmer based on their needs, desire and urgency.